2019
DOI: 10.9734/afsj/2019/v8i329994
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perception on Irrigation Farming and the Factors Influencing Access to and Size of Irrigable lands in Northern Region, Ghana

Abstract: Aim: The impacts of climate change and variability requires proactive and reactive adaptation. The high reliance of farmers on rainfed agriculture leads to their high vulnerability to climate change. As an agrarian economy, irrigation farming system is an essential proactive and/or reactive strategy for the increasing erratic rainfalls in Northern Ghana. This study analyzed the perceptions of smallholder farmers on irrigation farming and the factors that influence access to and size of irrigable lands among co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…Understanding land ownership is critical to agriculture productivity since primary land ownership is positively associated with decisions on land allocation to crops and technology adoption [22,24]. Kudadze, et al [25] maintained that irrigation farming in Ghana is very limited, which was confirmed in this study, where 60% of the farmers did not have access to irrigation. Similar results were reported by van Asselt,et al [4].…”
Section: Household Socio-economic Characteristics and Demographic Pro...supporting
confidence: 66%
“…Understanding land ownership is critical to agriculture productivity since primary land ownership is positively associated with decisions on land allocation to crops and technology adoption [22,24]. Kudadze, et al [25] maintained that irrigation farming in Ghana is very limited, which was confirmed in this study, where 60% of the farmers did not have access to irrigation. Similar results were reported by van Asselt,et al [4].…”
Section: Household Socio-economic Characteristics and Demographic Pro...supporting
confidence: 66%
“…Moreover, key informant interview participants explained that SSI is socially acceptable and applicable to communities without any social, cultural, or religious restrictions. Similar with this result a previous study indicates the social acceptability of irrigation since it does not clash with cultural and religious rules [44]. The adoption of new agricultural practices and technologies is influenced by different social factors, including religious laws, values, norms, taboos, and customs.…”
Section: Advances In Agriculturesupporting
confidence: 89%
“…In contrast with this result, the empirical study by Lebeta [27] indicates that lack of access to market and market information had a significant and adverse influence on irrigation adoption by farmers. The other study conducted by Kudaze et al [44], reports irrigation-user farmers practically understand the availability of high-market demand for irrigation products better than the nonuser respondents. Hence, the availability of high market demand is crucial in enhancing the profitability of irrigators and inspiring nonuser households to participate in the irrigation practices.…”
Section: Advances In Agriculturementioning
confidence: 90%
“…The study adopts an exploratory design (Kumar, 2019;Maxwell, 2012;Kothari, 2004) to gain insights into how information systems make information available and how user interaction with information produces actionable knowledge in rice-farming systems. An exploratory approach is espoused to enable an in-depth understanding of variables in the contextualised study essential for validating scientific conclusions (Jebb et al, 2017;Stebbins, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The scheme serves communities within Kumbungu District, with farmers accessing water for irrigation purposes. However, the majority of households still practice rainfed farming given the limited land area for cultivation under irrigation, amongst other reasons (Alhassan, Loomis, Frasier, Davies, & Andales, 2013;Kudadze, Imoru, & Adzawla, 2019;Zakaria, Abujaja, Adam, Nabila, & Mohammed, 2013). Of these, rice farmers, given the crop's copious water requirement, are at a high risk of crop failure, especially in rainfed farming systems.…”
Section: Background and Problem Definitionmentioning
confidence: 99%